Healthcare Providers’ Understanding and Performance in Stunting Prevention: A Study from Rural and Urban Primary Healthcare Facilities in Indonesia - Ramadhaniyati, Ramadhaniyati; Lestari, Lilis; Saito, Ruka; Tsuda, Akiko (International Journal of Child Health and Nutrition, 2026)
Background: Reducing stunting globally remains inadequate, with regional disparities persisting between rural and urban areas. This study aims to compare the knowledge and performance of healthcare providers (HCPs) in rural and urban primary healthcare facilities regarding the implementation of stunting prevention using a quantitative approach. It also explores further rural HCPs’ challenges through a qualitative study. Methods: A cross-sectional quantitative study involved 557 primary HCPs from rural and urban Indonesia from July to October 2023. Data were collected using a self-administered structured questionnaire. Descriptive statistical analysis and the Chi-Square test were conducted with IBM SPSS version 29. Additionally, a descriptive qualitative study was conducted in a rural area in January 2024, employing purposive sampling and semi-structured interviews with eight primary HCPs, which were analyzed using content analysis. Results: Compared to their urban counterparts, rural HCPs showed less knowledge of nutrition (p = 0.007) and stunting (p = 0.013), higher socio-cultural values that impact stunting (p = 0.009), ineffective implementation of stunting prevention (p = 0.013), and higher barriers in implementing stunting prevention (p < 0.001). Qualitative findings further revealed that weak awareness, capacity issues, and socio-cultural challenges constituted significant obstacles for rural HCPs. Conclusion: This study underscores the need for policymakers to prioritize the development of targeted intervention programs that enhance rural HCPs’ capacity in nutrition, cultural competency, advocacy, and communication. Policymakers must formulate effective policies and standardized, easy-to-implement guidelines for stunting prevention specifically to rural primary care settings.